Inflammatory and Metabolic Syndrome Biomarker Analysis of Vascular Outcomes in End-stage Renal Disease - Sweigert, Patrick J. (Int J Angiol, 2016)
End-stage renal disease (ESRD) presents a complex syndrome in which inflammatory and metabolic processes contribute to disease progression and development of comorbid conditions. Over $1 trillion is spent globally on ESRD care. Plasma samples collected from 83 ESRD patients prior to hemodialysis were profiled for metabolic and inflammatory biomarker concentrations. Concentrations were compared between groups with and without history of stroke, acute coronary syndrome (ACS), congestive heart failure (CHF), and coronary artery disease (CAD). The 25 patients (30.1%) with history of stroke demonstrated decreased plasma interferon-γ levels (p = 0.042) and elevated plasma resistin, interleukin (IL)-1α, and leptin levels (p = 0.008, 0.021, 0.026, respectively) when compared with ESRD patients without history of stroke. The 14 patients (16.9%) with history of ACS demonstrated elevated plasma IL-6 levels (p = 0.040) when compared with ESRD patients without history of ACS. The 30 patients (36.1%) with history of CHF demonstrated decreased plasma leptin levels (p = 0.031) and elevated plasma IL-1β levels (p = 0.042) when compared with ESRD patients without history of CHF. Finally, the 39 patients (47.0%) with history of CAD demonstrated elevated plasma IL-1α levels (p = 0.049) when compared with ESRD patients without history of CAD. Plasma biomarker concentration disturbances were observed in ESRD patients with history of stroke, ACS, CHF, and CAD when compared with ESRD patients without such history. Proinflammatory biomarker elevations were seen in stroke, ACS, CHF and CAD, while adipocytokine aberrations were observed in both stroke and CHF. These studies demonstrate that biomarker profiling of vascular comorbidities in ESRD may provide useful diagnostic and prognostic information in the management of ESRD patients.